Interpersonal difficulties as a risk factor for athletes' eating psychopathology - Shanmugam, V.; Jowett, S.; Meyer, C. (Scandinavian Journal of Medicine & Science in Sports, 2014)
The present study sought to determine the predictive role of interpersonal difficulties on eating psychopathology among competitive British athletes (ranging from university to international competition level). A total of 122 athletes (36 males and 86 females) with a mean age of 21.22 years (SD = 4.02), completed a multisection questionnaire that measured eating psychopathology, attachment styles, and quality of relationships with parents, coaches and teammate over a 6-month period. Partial correlations revealed that when controlling for baseline eating psychopathology, only the quality of the relationship with coach and closest teammate were related to athletes' eating psychopathology 6 months later. Subsequent hierarchical multiple regression analyses demonstrated that athletes' eating psychopathology was only predicted by perceived levels of interpersonal conflict with the coach. The current findings provide evidence to suggest that conflict within the coach-athlete relationship is a potential risk factor for eating disorders among athletes and thus it would seem appropriate to raise awareness for its potentially toxic role in athletes' eating psychopathology.